Answer:
![\displaystyle (x-3)^2 + (y+2)^2 = 36](https://img.qammunity.org/2022/formulas/mathematics/college/gelavu6hoxnwygq4om8m7cvz5curp67o2u.png)
Explanation:
We want to write the equation of a circle with a center at (3, -2) and a radius of 6 units.
Recall that the equation of a circle is given by:
![\displaystyle (x-h)^2 + (y-k)^2 = r^2](https://img.qammunity.org/2022/formulas/mathematics/college/20fm6df0456689cbbbxw9u9toawj7ui6uy.png)
Where (h, k) is the center and r is the radius.
Since our center is at (3, -2), h = 3 and k = -2. r = 6. Substitute:
![\displaystyle (x-(3))^2 +(y-(-2))^2 = (6)^2](https://img.qammunity.org/2022/formulas/mathematics/college/8idfot8iltkzexlcrhzy86x3oe2gd3nknw.png)
Simplify:
![\displaystyle (x-3)^2 + (y+2)^2 = 36](https://img.qammunity.org/2022/formulas/mathematics/college/gelavu6hoxnwygq4om8m7cvz5curp67o2u.png)
In conclusion, the equation of the circle will be:
![\displaystyle (x-3)^2 + (y+2)^2 = 36](https://img.qammunity.org/2022/formulas/mathematics/college/gelavu6hoxnwygq4om8m7cvz5curp67o2u.png)